The snowman sign in a patient with pituitary tumor apoplexy - Khulood Bukhari; Vandhna Sharma; Sonia Gupta; Abbas Motazedi (Greater Baltimore Medical Center, 2021)
Pituitary apoplexy is a life-threatening complication that may result from hemorrhage or infarction of a pituitary adenoma. Neuroimaging may reveal a snowman-like or 'figure of 8ʹ configuration as a result of bilateral indentation of the tumor by the sellar diaphragm.